STUDI DAYA DUKUNG STABILISASI TANAH LEMPUNG MENGGUNAKAN CAMPURAN ABU KAYU - Pristianto, Hendrik; Rokhman, Rokhman; irman, irman (JURNAL MOMEN TEKNIK SIPIL SURYAKANCANA, 2022)
In highway construction work requires a strong and stable subgrade. But in reality the subgrade that is often encountered is subgrade with low support, so it does not meet the requirements when used for road pavement construction. One way to overcome this problem is to do stabilization, namely by using an additive in the form of wood ash. The purpose of this study was to identify how much influence wood ash had on the CBR value of the soil. This research is expected to provide information regarding the feasibility of soil stabilization in Sorong City by using wood ash from wood waste so that it can be used appropriately. For this reason, it is necessary to conduct a study on the use of wood burning residues as a stabilizing material and is expected to increase the carrying capacity of the soil. This research will be carried out by means of stabilization with variations in the mixture content of 3%, 6%, 9%, 12% and 15%. The type of soil that will be used in this study comes from Jalan Moyo, East Sorong District, Sorong City. Next will be testing specific gravity, atterberg limit, compaction test and CBR on each variation of mixing. The results of this study indicate that stabilization of clay soil using wood ash can increase the bearing capacity of the soil, namely where the CBR value of the original soil is 7.32%, which increases with each addition of the percentage of wood ash content.